Translation of Cultural Terms in Mirah of Banda Novel - Nurfitriani . Padang; Sumarsih . .; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2021)
ABSTRACTThis research, entitled Translation of Cultural Terms in Mirah of Banda Novel, deals with the analysis  analysis of the translation of cultural terms in the novel. The main objectives of the study were to answer the research problems under study; which is to identify categories of cultural terms  which found in the novel,Mirah of Banda . The data were collected from  Mirah dari Banda, as the SL; and Mirah of Banda, as the TL, by applying documentation method of close-reading and note-taking technique. Then, the data was classified into some groups according to their categories  and displayed in table. The data was descriptively analyzed based on theories from Newmark to find out the answer of the research problems. The result of the data analysis shows that there were six categories of cultural words in Mirah of Banda Novel namely (1) ecology (2) material culture, (3) social culture, (4) custom, concept,( 5) gestures and habits and (6) Indonesian metaphor and Indonesian metaphor was the new categories found besides the prior categories which is proposed by Newmark.   In detail, it is dominated of ecology in 33.75% (27 data), material culture 25.00%  (20 data), social culture 23.75% (19 data), custom 6, 25% (5 data), concept 6. 25% (5 data),gestures and habits 1. 25 % (1 datum), and Indonesian Metaphor 3.75% (3 data) and The cultural words in Mirah of Banda Novel were translated by applying  ten  strategies, namely: transference (12%), cultural equivalent (2,5%), functional equivalent (10%), descriptive equivalent (2,5%), synonymy (20%), through translation (22,5%), modulation (6, 25%),compensation (5%), couplet (1, 25%), as a new strategy, trope change (3,75%)Keywords: Translation, Cultural Terms, Mirah of Banda Novel,Concept